2015
DOI: 10.1103/physrevlett.114.235001
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniversality and Finite Dissipation in Decaying Magnetohydrodynamic Turbulence

Abstract: A model equation for the Reynolds number dependence of the dimensionless dissipation rate in freely decaying homogeneous magnetohydrodynamic turbulence in the absence of a mean magnetic field is derived from the real-space energy balance equation, leading to Cε = Cε,∞ + C/R− + O(1/R 2 − )), where R− is a generalized Reynolds number. The constant Cε,∞ describes the total energy transfer flux. This flux depends on magnetic and cross helicities, because these affect the nonlinear transfer of energy, suggesting th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…Those works showed that, in a sense, vorticity and magnetic flux, both being Lagrangian invariants, can also undergo a cascade. Recent numerical studies [41][42][43] have also presented evidence in support of the existence of a zeroth-law for the total energy in MHD turbulence. All major theories of MHD turbulence [44][45][46][47] implicitly rely on the existence of a dissipative anomaly.…”
Section: The Cascadementioning
confidence: 87%
“…Those works showed that, in a sense, vorticity and magnetic flux, both being Lagrangian invariants, can also undergo a cascade. Recent numerical studies [41][42][43] have also presented evidence in support of the existence of a zeroth-law for the total energy in MHD turbulence. All major theories of MHD turbulence [44][45][46][47] implicitly rely on the existence of a dissipative anomaly.…”
Section: The Cascadementioning
confidence: 87%
“…They provide a framework in which the main features of the flow such as the forcing, the kinematic and magnetic viscosities, or the initial and boundary conditions may be precisely controlled. As such, they have been extensively used for the study of MHD turbulence, under a wide range of conditions [67][68][69][70][71][72][73]. In the end, DNS give access to all components of the relevant fields on a grid.…”
Section: Application To Turbulent Numerical Datamentioning
confidence: 99%
“…A comparison with [18] revealed that the dimensionless dissipation rate saturates to a finite value but the level of saturation depends on the strength of initial cross-correlation. Recently, Linkmann et al [32,33] have performed a series of investigations for similar analysis in isotropic MHD. By fitting a model equation, an asymptotic value of dimensionless dissipation rate, C ǫ,∞ = 0.265 ± 0.013, was found for nonhelical decaying MHD with no mean field.…”
Section: Introductionmentioning
confidence: 99%